Indigenous peoples rights under international law - Adcock, Fleur; Charters, Claire (The New Zealand Yearbook of International Law, 2010)
In 2010 Indigenous peoples' rights continued to feature in discussions in a variety of international fora. Indigenous peoples' traditional knowledge (TK) associated with genetic resources (GR) were discussed under the Convention on Biological Diversity (CBD); under the auspices of the World Intellectual Property Office (WIPO) and within the World Trade Office (WTO). The United Nations (UN) General Assembly's Declaration on the Rights of Indigenous Peoples (Indigenous Peoples' Declaration) featured in debate under the UN Framework Convention on Climate Change (UNFCCC); the UN General Assembly's Third Committee; the work of the UN mechanisms with a specific mandate concerning Indigenous peoples; and, in a landmark ruling of the African Commission on Human and People's Rights (African Commission), was adopted by the African Union. International human rights monitoring bodies also advanced their jurisprudence on the rights of Indigenous peoples.
Keywords: UNDRIP; civil Rights; crown policy; discrimination; takutai moana; tiriti o waitangi/treaty of waitangi; united nations